The Use of Genre-Based Approach (GBA) in Teaching Reading Comprehension in Terms of Skimming - Munawir; Dian Riani Said Muh. Said (Inspiring: English Education Journal, 2022)
Some Indonesian students are found that they have low reading skills. This difficulty causes them in boredom and less motivation to learn English. This research aimed to know the use of genre-based approach (GBA) in teaching reading in terms of skimming at the eighth grade students of SMP Negeri 1 Sibulue. The researcher applied classroom action research. It had two cycles that consisted of planning, action, observation, and reflection phase. The researcher found that GBA is a good approach to increase the students’ reading comprehension. Students’ activeness in teaching and learning process improved significantly through the use of GBA. The researcher concluded that GBA was able and significant in increasing the students’ reading comprehension. Keywords: Genre-Based Approach (GBA), students’ reading comprehension